Tribological performance Optimization of Al2024-TiB2 composites using Grey-Taguchi approach. (2nd November 2022) - Dey, Dipankar; Bhowmik, Abhijit; Biswas, Ajay
ABSTRACT: Present investigation aims at the fabrication of aluminium matrix composites reinforced with different weight percentages of titanium diboride (TiB2 ) particles and characterisation of their tribological behaviour. Wear tests are carried out on a pin-on-disc tribotester with four different process parameters viz. wt-% of reinforcement, load, sliding velocity and sliding distance. For assessing the tribological performance of composites, grey relational analysis is adopted. The percentage significance of all the parameters on tribological performance has also been evaluated by analysis of variance. Based on Grey-Taguchi approach, the optimal parametric combination is 9 wt-% of reinforcement, 10 N load, 2 m s −1 sliding velocity and 1000 m sliding distance. The optimal parametric combination based on the highest ranking of grey relational grade is validated by a confirmation experiment. Based on the results, it can be concluded that Grey-Taguchi method is an effective tool used for optimising the tribological performance of Al2024-TiB2 composites.